Speaking sign or acting device? Reading and using the Christogram in Byzantium. Issue 1 (2nd January 2023) - Maguire, Henry
Abstract: The Christogram, the sign combining the letters chi with a rho, an iota, or a cross, became extremely common in Early Christian art, in both the East and the West, where it was freighted with multiple and overlapping meanings, whether theological, imperial, or both. The Christogram's capacity to create meaning through letters and words was elaborated upon in later medieval art in the West, in a way that had no counterparts in Byzantium. In the medieval West, the sign of the Chi Rho sometimes assumed the status of an intellectual puzzle, the solution of which could lead to spiritual understanding. There was nothing comparable in the art of Byzantium. Following the crisis of iconoclasm in the East, the type of Christogram that combined the chi or the cross with a rho, creating a loop at the top of the vertical bar, almost completely disappeared from the monumental decoration of Byzantine churches, even while other types survived. One major problem was that the rho made the Christogram resemble ring signs, which were ubiquitous in Eastern magic from antiquity to the end of the Middle Ages. The issue of magic had become particularly sensitive in the Byzantine Church as a result of the iconoclastic dispute, in which both sides, the supporters and the opponents of images, accused the other of sorcery. In the Byzantine East, the removal of the loop from the upright letter stripped the Christogram not only of its more overt magical associations but also of many possibilities for word-play and meaning that were exploited by artists in the West.